Brassica napus Mediator Subunit16 Induces BnMED25- and BnWRKY33-Activated Defense Signaling to Confer Sclerotinia sclerotiorum Resistance - Hu, Huizhen; Tang, Yiwei; Wu, Jian; Chen, Feizhi; Yang, Yidan; Pan, Xuancheng; Dong, Xiang; Jin, Xianda; Liu, Sheng; Du, Xuezhu (Frontiers in Plant Science, 2021)
The plant mediator is a highly conserved protein complex that interacts with transcription factors (TFs) and RNA polymerase II (RNAP II) to relay regulatory information during transcription. Plant immune response is one of the biological processes that is orchestrated by this regulatory mechanism. Brassica napus, an important oil crop, is severely attacked by a devastating disease Sclerotinia stem rot. Here, we explored broad-spectrum disease resistant roles of B. napus mediator subunit 16 (BnMED16) and its host defense mechanism against fugal pathogen Sclerotinia sclerotiorum. We found that BnMED16 expression was significantly increased by S. sclerotiorum infection, and its homologous overexpression resulted in rapid and comprehensive defense responses from the beginning to the end. This affected signal transduction with multiple channels including pathogen recognition, intracellular Ca2+ concentration, reactive oxygen species (ROS) accumulation and clearance, and activation of mitogen-activated protein kinase (MAPK) signaling cascades initially. Subsequently, pathogen-/defense-related genes and hormone-responsive pathways were highly activated, which resulted in enhanced cell wall and secretion of defense proteases. Furthermore, the biochemical analysis showed that BnMED16 interacts with BnMED25 and BnWRKY33. Addiontally, BnMED25 also interacts with TFs BnMYC2, BnCOI1, and BnEIN3 of the JA/ET signal transduction pathway. Taken together, we proposed a hypothetical model that BnMED16 confers S. sclerotiorum resistance by enhancing BnMED25-mediated JA/ET defense pathways and BnWRKY33-activated defense signaling in B. napus. The BnMED16 overexpressing lines with enhanced broad-spectrum disease resistance could be useful for breeding Sclerotinia-resistant oilseed rape varieties, as well as serving as basis for further strategy development in resistance breeding.